Charter School Competition, Organization, and Achievement in Traditional Public Schools - Davis, Tomeka M. (Education Policy Analysis Archives, 2013)
Market models of education reform predict that the growth of charter schools will infuse competition into the public school sector, forcing traditional public schools to improve the practices they engage in to educate students. Some scholars have criticized these models, arguing that competition from charter schools is unlikely to produce significant change among public schools. Using data from the Early Childhood Longitudinal Study – Kindergarten Class, I attempt to identify potential mechanisms linking charter competition to achievement in traditional public schools. The results provide little support for the market model. Competition from charter schools is not associated with reading or math scores, and is only associated with three of ten organizational measures.  There is some support for an indirect relationship between math achievement and competition through reductions in teacher absenteeism, but these results fall short of meeting conventional thresholds for statistical significance.